Analisis Penanganan Tindak Pidana Penganiayaan yang Dilakukan Oknum Bangsawan di Kecamatan Rindi Kabupaten Sumba Timur - Alesandro Umbu Rangga Pahada; Karolus Kopong Medan; Bhisa Vhitus Wilhelmus (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The resolution of cases solved by maramba against the people or faced with various legal, social, cultural, and economic obstacles. Limited access to law enforcement and low legal knowledge make victims reluctant to seek justice. The research used is empirical legal research or empirical juridical research. Data collection for this research is interviews, observations and document studies. The data to be collected is then processed using the observation method. The results of the study show that the choice of customary resolution that prioritizes reconciliation also makes cases rarely processed through formal law. Economic dependence on maramba further weakens the position of ata. Violations committed by maramba (king) against the ata (lower) people in Rindi District, East Sumba, can be resolved through two channels: criminal law and customary law. Criminally, tournaments are regulated in Article 351 of the Criminal Code and can be reported to the authorities. However, people more often choose customary resolution through mediation by traditional elders (rato) who emphasize compensation or peace rituals. Social inequality, maramba dominance, economic dependence, and cultural pressure make it difficult for the ata people to fight back. They are reluctant to report because they are afraid, do not understand the law, and believe more in customary resolutions which are considered to maintain social harmony.